THE EFFECT OF REGIONAL RESTRIBUTION, RESULTS OF SEPARATED REGIONAL MANAGEMENT AND SILPA ON REGIONAL ORIGINAL INCOME WITH ECONOMIC GROWTH AS A VARIABLE INTERVENING - Yois Nelsari Malau; Kelly Halim; Fela Zori; Tevin Tevin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background : The purpose of this study is to evaluate how the influence of regional management and different regional levies, as well as silpa on PAD in the regencies/cities of North Sumatra Province during the 2017-2019 period, either partially or simultaneously. Method : Multiple linear regression analysis approach is used in the research process. The research findings show that the regional levy variables and the results of regional management that are separated partially affect PAD with economic growth as an interverning variable in the Regency/City of North Sumatra Province during the 2017-2019 period. Result : For the period 2017-2019, the Silpa variable has a partial effect on PAD when economic growth is used as an interverning variable in the Regency/City of North Sumatra Province. Conclusions : The economic growth variable as an intervening partially has no effect on PAD in the Regency/Municipality of North Sumatra Province for the 2017-2019 period.